PENGEMBANGAN LEMBAR KERJA PRAKTIKUM ELEKTRONIK BERBASIS 3D PAGEFLIP PROFESSIONAL PADA PRAKTIKUM DASAR-DASAR KIMIA ANALITIK - Andi Rabuandika; Rody Putra Sartika; Rahmat Rasmawan (Universitas Muhammadiyah Pontianak, 2021)
The presentation of teaching materials is not only limited to print media but already utilizes digital media, so it is necessary to develop a teaching material in the form of an electronic practicum worksheet using an application, namely the 3D PageFlip Professional application. This study aims to determine the feasibility of the 3D PageFlip Professional based Electronic Practicum Worksheet (e-LKP) in the Practical Basics of Analytical Chemistry through the results of validation and lecturer responses to the developed 3D PageFlip Professional-based Electronic Practicum Worksheet (e-LKP). The research and development method used leads to one of the Borg and Gall development models modified by Sugiyono. The research subjects involved consisted of experts (material experts, media experts, and linguists) and Analytical Chemistry Lecturers. The expert provides an assessment of the validity of the material, the suitability of the e-LKP design, conformance with Indonesian language rules, while the lecturer response test contains material aspects, language aspects, and media aspects of the 3D PageFlip Professional-based e-LKP developed by researchers. The results obtained are the feasibility of e-LKP based on 3D PageFlip Professional. Based on the expert's assessment, it is predicted that the feasibility level is very high with the percentage of content aspects (88.88%), presentation aspects (98.61%), language aspects (89.57%), and media aspects (90.83%). Meanwhile, the lecturers' response to the 3D PageFlip Professional-based e-LKP was (86.77%) with very high criteria.Keywords: Development, Electronic Practicum Worksheet, 3D PageFlip Professional, Basics of Analytical Chemistry.